1999
DOI: 10.1107/s0907444998017703
|View full text |Cite
|
Sign up to set email alerts
|

Combining direct methods with isomorphous replacement or anomalous scattering data. VIII. Phasing experimental SIR data with the replacing atoms in a centrosymmetric arrangement

Abstract: A multisolution direct method has been proposed to resolve the phase ambiguity intrinsic in single isomorphous replacement data of proteins with the replacing atoms in a centrosymmetric arrangement. The phase ambiguity of each re¯ection is in fact a`sign ambiguity' of the phase difference between the phase of the native protein and that of the replacing atoms, i.e. AE |Á9| = 9 À 9 H . The P + probability formula can be used to derive the signs. The multisolution phasing procedure is initiated using random star… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Similar investigations were reported by different authors during 1960s and 1970s 33–38. From the early 1980s to the early 2000s, the combination of direct methods with SAD/SIR data was emphasized in direct‐method research worldwide 39–63. The first application of direct‐method SAD phasing in solving originally unknown protein structures was reported in 1999 56 with data at 2.1 Å resolution.…”
Section: Direct Methods In Macromolecular Crystallographysupporting
confidence: 67%
See 1 more Smart Citation
“…Similar investigations were reported by different authors during 1960s and 1970s 33–38. From the early 1980s to the early 2000s, the combination of direct methods with SAD/SIR data was emphasized in direct‐method research worldwide 39–63. The first application of direct‐method SAD phasing in solving originally unknown protein structures was reported in 1999 56 with data at 2.1 Å resolution.…”
Section: Direct Methods In Macromolecular Crystallographysupporting
confidence: 67%
“…The test on Hg‐derivative SIR data 55 showed that, owing to the centric arrangement of the Hg‐substructure, conventional SIR phasing methods failed to break the phase ambiguity. However, direct‐method SIR phasing followed by density modification produced an acceptable result (see Fig.…”
Section: Direct Methods In Macromolecular Crystallographymentioning
confidence: 99%
“…The structure of MKLN 1-205 was solved by sulfur SAD with the HySS (Hybrid Substructure Search) submodule of the Phenix package (Adams et al, 2002) together with the Oasis program of the CCP4 suite (Liu et al, 1999;Winn et al, 2011). The substructure was refined using SHARP (Bricogne et al, 2003), and iterations between automatically building partial models with the Buccaneer software (Cowtan, 2006) using the modified map and refinement of the partial model and density modification in SHARP finally led to an improved model, which was then completed manually and further refined using REFMAC (Skubak et al, 2004).…”
Section: Structure Solutionmentioning
confidence: 99%
“…A direct method to resolve this ambiguity has been reported using experimental SIR data to 2.0 Ð resolution for the small protein avine pancreatic polypeptide (previous work on the method used synthetic ideal data). 106 A four-phase structure invariant (4PSI) can be derived from four pairs of equivalent re£ections from two isomorphous datasets; the probability distribution of 4PSIs can be derived by integration of direct methods with isomorphous replacement and their reliability was shown to be comparable with that for 3PSIs. 107…”
Section: Heavy Atom Methodsmentioning
confidence: 99%